The effect of non-informative spatial sounds on haptic scene recognition - NEWELL, FIONA (My University, 2013)
Previous studies found that performance in tactile or haptic spatial tasks improved when non-informative visual information was available, suggesting that vision provides a precise spatial frame to which tactile information is referred. Here, we explored whether another intrinsically spatial modality, audition, can also affect haptic recognition. In all experiments, blindfolded participants first learned a scene through touch and were subsequently required to recognise the scene. We found no effect on haptic performance when white noise stimuli were presented from specific locations (Experiment 1). However, performance was significantly reduced by pure tone stimuli presented from the same locations (Experiment 2), moreover, these tones disrupted recall but not encoding of the haptic scene (Experiment 3). In Experiment 4, we found that spatial rather than non-spatial auditory information was required to affect haptic performance. Finally, in Experiment 5 we found no specific benefit for familiar sound cues over unfamiliar or no sounds on haptic spatial performance. Our findings suggest that, in contrast to vision, auditory information is unlikely to have sufficient spatial precision therefore disrupting the spatial representation of haptic information. Our results add to a growing body of evidence for multisensory influences in the perception of space.
PUBLISHED
Keywords: multisensory; audition; haptics; scene recognition; Neuroscience